Conceptual foundations of the model of optimization of speech self-expression at pre-school educational establishments (Pedagogy of Higher and Secondary Education, 2013)
Anischuk A. N. Conceptual foundations of the model of optimization of speech self-expression at pre-school educational establishments.The article reveals basic conceptual foundations of the model of optimization of speech self-expression at pre-school educational establishments.
Keywords: conceptual foundations; speech self-expression; model of optimization; language environment; language culture